Overexpression of cancer susceptibility candidate 2 inhibited progression of hepatocellular carcinoma cells. Issue 6 (26th October 2018) - Gao, Xiang; Du, Haijun; Zhang, Ruoxi; Li, Cong; Wang, Hongguang; Xuan, Qi; Liu, Diangang
Abstract: Objective: Our study was aimed to investigate the effect of cancer susceptibility candidate 2 (CASC2) on the proliferation, cell cycle, apoptosis, and metastasis of hepatocellular carcinoma (HCC) cells. Methods: CASC2 expression in tumor tissues and HCC cells was tested by quantitative real‐time polymerase chain reaction. After manipulating the expression of CASC2 in Hep3B and HepG2 cells, cells viability, including proliferation, apoptosis, cell‐cycle distribution, migration, and invasion were examined by colony formation assay, flow cytometry, wound‐healing assay, and transwell assay, respectively. The expression levels of proteins associated with the cell cycle and AKT/mTOR pathway were measured by the western blot. Stably transfected HepG2 cells were used to construct nude mice models, and tumorigenesis was evaluated to investigate the in vivo functions of CASC2 in HCC progression. Results: In tissues and cells of HCC, decreased CASC2 expressions were confirmed. Overexpression of CASC2 made cell cycle stagnated at G0/G1 phase and induced apoptosis. Meanwhile, the overexpression of CASC2 played significant roles in inhibiting the proliferation, migration, and invasion of HCC cells. Furthermore, In vivo experiment indicated that CASC2 restrained the growth of tumors. Conclusion: Our study suggested that CASC2 promoted cell apoptosis and suppressed cell growth and metastasis in HCC, indicating that CASC2 might be a useful biomarker of HCC. Abstract : 1. We demonstrated that cancer susceptibility candidate 2 (CASC2) promoted cell apoptosis and suppressed cell viability and metastasis in hepatocellular carcinoma (HCC). 2. This finding will improve the understanding of the mechanism involved in cancer progression and provide novel targets for the molecular treatment of HCC.